2019
DOI: 10.1186/s12967-019-2098-6
|View full text |Cite
|
Sign up to set email alerts
|

CD36 promotes the epithelial–mesenchymal transition and metastasis in cervical cancer by interacting with TGF-β

Abstract: BackgroundAccumulating evidence indicates that CD36 initiates metastasis and correlates with an unfavorable prognosis in cancers. However, there are few reports regarding the roles of CD36 in initiation and metastasis of cervical cancer.MethodsUsing immunohistochemistry, we analyzed 133 cervical cancer samples for CD36 protein expression levels, and then investigated the correlation between changes in its expression and clinicopathologic parameters. The effect of CD36 expression on the epithelial–mesenchymal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 27 publications
2
68
0
Order By: Relevance
“…In the tumor microenvironment, cervical cancer-associated fibroblasts enhance the ability of cervical cancer cells to invade by secreting TGF-β ( Nagura et al, 2015 ). Deng et al (2019) revealed that CD36 binds to TGF-β to promote EMT, which leads to the migration and invasion of cervical cancer. Twist also regulates EMT via the TGF beta signaling pathway and promotes the migration of cervical cancer cells ( Fan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the tumor microenvironment, cervical cancer-associated fibroblasts enhance the ability of cervical cancer cells to invade by secreting TGF-β ( Nagura et al, 2015 ). Deng et al (2019) revealed that CD36 binds to TGF-β to promote EMT, which leads to the migration and invasion of cervical cancer. Twist also regulates EMT via the TGF beta signaling pathway and promotes the migration of cervical cancer cells ( Fan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…CD36 contributes to the progression and metastatic potential of cancer by several mechanisms, such as activation of cancer stem cells, epithelial-to-mesenchymal transition, and chemoresistance [35,36].…”
Section: Cd36 Promotes Tumor Metastasis In Pancreatic Cancermentioning
confidence: 99%
“…Taking into consideration that these two markers were separately described in different studies [35,53,71,79] as conferring an invasive phenotype, silencing both their expression could affect the physiopathology of the disease.…”
Section: Why Examine Concomitant Expression Of Cd36 and Cd97s? (Why Bmentioning
confidence: 99%
“…The majority of early cancer is detected via refined detection technology, and the mortality of CC has apparently declined, and the prognosis rate has been elevated 6 . However, patients with advanced CC still have unpleasant endings because of the high onset of metastasis, which is a main element affecting the prognosis of patients 7 . Cancer stem cells strengthen tumor‐initiating and self‐renewing abilities 8 .…”
Section: Introductionmentioning
confidence: 99%
“…6 However, patients with advanced CC still have unpleasant endings because of the high onset of metastasis, which is a main element affecting the prognosis of patients. 7 Cancer stem cells strengthen tumor-initiating and self-renewing abilities. 8 At present, no therapies are able to eliminate cancer stem cells, and their presence leads to poor prognosis in CC.…”
mentioning
confidence: 99%